Geomorphological evidence of different glacial stages in the Martial cirque, Fuegian Andes, Southernmost South America - Planas, Xavier (2002)
The geomorphological features of a cirque partially occupied by receding ice bodies are presented as evidences of different glacial stages in the Fuegian Andes summits since the Last Glaciation (IOS 2). A glacierization scheme involving: (i) regional glacier accumulation basin; (ii) glacier individualization from a main regional; (ii) a stillstand during the general retreat and (iii) two advancing stages are suggested. Geomorphic and sedimentary units, named Martial I, II, III and IV, have been distinguished as a consequence of the glacial scheme. Unfortunately, the lack of datable materials has impeded establishment of an absolute chronology. Recognized glacier advances in the region are discussed. The palaeoclimatic framework for the surroundings, based on previous studies, is presented.